2011
DOI: 10.1177/0020872811421620
|View full text |Cite
|
Sign up to set email alerts
|

Burnout, workplace support, job satisfaction and life satisfaction among social workers in Spain: A structural equation model

Abstract: This article analyses the effects of burnout in a sample of social workers from Malaga, Spain. The results obtained with the structural equations model confirm that burnout has a negative influence on workplace support, job satisfaction and life satisfaction and that workplace support has a positive influence on job satisfaction. Workplace support acts as mediator variable between burnout and job satisfaction and buffers the negative effects of burnout on job satisfaction and life satisfaction among social wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
65
0
13

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(91 citation statements)
references
References 49 publications
6
65
0
13
Order By: Relevance
“…In this study, social support from supervisors, family and friends was found to have negative relationships with emotional exhaustion and depersonalization and positive relationships with personal accomplishment among RNs pursuing an advanced degree. These results were consistent with previous findings that social support reduced the level of burnout among workers in service professions and social workers (Hombrados‐Mendieta & Cosano‐Riva , Hamama , Wang et al . ).…”
Section: Discussionsupporting
confidence: 93%
“…In this study, social support from supervisors, family and friends was found to have negative relationships with emotional exhaustion and depersonalization and positive relationships with personal accomplishment among RNs pursuing an advanced degree. These results were consistent with previous findings that social support reduced the level of burnout among workers in service professions and social workers (Hombrados‐Mendieta & Cosano‐Riva , Hamama , Wang et al . ).…”
Section: Discussionsupporting
confidence: 93%
“…Maslach and Jackson (1981) state that the activation of MBI's three sub-dimensions, being emotional exhaustion, depersonalization and reduced personal accomplishment sub-scales may cause work-related problems such as absenteeism and demoralization in the individual's life, alongside health problems and serious consequences such as an overall decrease in life satisfaction. In this research, the conclusion that there are negatively meaningful relations between life satisfaction and MBI-SS's three sub-scale scores show consistencies with the results of the research in literature conducted by university students (Chan, 2010;Çapri et al, 2012) and different professional workers employees (Anand and Arora, 2009;Avşaroğlu, Deniz and Kahraman, 2005;Çakınberk, 2011;Demerouti et al, 2000;Gümüş, 2006;Hayes and Weathington, 2007;Hombrados-Mendieta and Cosano-Rivas, 2011;Lee et al, 2004;Örkün, 2011;Özkan and Özdevecioğlu, 2012;Şahin, 2008;Şahin, 2010;Ünal, Karlıdağ and Yoloğlu, 2001) indicating that there is such a relation, pointing at the fact that the higher students' life satisfaction gets, the more their burnout will decrease. In such case, it is considered that if students' life satisfaction can be increased, from serious consequences of the problems (related to health and work) result from the burnout may be avoided.…”
Section: Discussionsupporting
confidence: 83%
“…According to Lambert, Hogan and Altheimer (2010), there is a negatively meaningful relation between burnout and life satisfaction. A great many research in literature indicating that such relation is present both for university students (Chan, 2011;Çapri, Özkendir, Özkurt and Karakuş, 2012) and workers from varying professions (Anand and Arora, 2009;Avşaroğlu, Deniz and Kahraman, 2005;Çakınberk, 2011;Demerouti, Bakker, Nachreiner and Schaufeli, 2000;Gümüş, 2006;Hayes and Weathington, 2007;Hombrados-Mendieta and Cosano-Rivas, 2011;Lee, Hwang, Kim and Daly, 2004;Örkün, 2011;Özkan and Özdevecioğlu, 2012;Şahin, 2008;Şahin, 2010;Ünal, Karlıdağ and Yoloğlu, 2001) are attention drawing.…”
Section: Introductionmentioning
confidence: 99%
“…Eighteen of the nineteen studies included an LIZANO affective or psychological well-being measure ranging from job satisfaction and life satisfaction to depression and anxiety. Job satisfaction was the most studied affective well-being outcome, with a total of nine articles including it as dependent variable (Bhana et al, 1996;Burke et al, 2010;Hombrados-Mendieta et al, 2011;Iglesias et al, 2013;Jaharami et al, 2014;Jayarante et al, 1996;Koeske, 1995;Maslach et al, 1988;Um et al, 1998). All studies examining job satisfaction as a well-being outcome used a cross-sectional design.…”
Section: Synthesis Of Studies Affective/psychological Well-beingmentioning
confidence: 99%